A comparative study of ozonation on aqueous reactive dyes and reactive‐dyed cotton. (17th February 2021) - Li, Mengru; He, Zhenglei; Xu, Jie
Abstract: Ozonation is increasingly being used and reported in recent years. This paper investigates ozonation on aqueous reactive dyes and their dyed cotton comparatively. The effects, including pH, temperature and initial dye concentration (for aqueous dyes)/water pick‐up (for dyed cotton), on Reactive Blue FL‐RN, Reactive Red FL‐2BL and Reactive Yellow FL‐2RN, were studied via Fourier Transform–infrared spectroscopy, ultraviolet‐visible absorption and k/s curves. The kinetic results indicated that all the aqueous dyes were of pseudo‐first order kinetics, while dyed cotton represented pseudo‐secondary or pseudo‐third order kinetics. Based on their different mechanisms, there was a dramatic gap between dyes and dyed cotton in ozonation performance. The curve of rate constant vs pH of dye ozonation exhibited a U‐shape with the minimum value at pH 7, but for dyed cotton ozonation, the curve showed a Λ‐shape optimised at pH 10. Also, high temperature resulted in hydrolysis of dyes in aqueous solution, whereas this was not applicable to dyed cotton. The effect of pick‐up (0%‐150% with an interval of 75%) on reactive‐dyed cotton was greater than the effect of initial dye concentration (which varied from 120 to 40 mg/L) on the colour yield of aqueous reactive dyes.